Assessment of Immunization Status of 12-23 Month Children in Urban Slums in Solapur Maharashtra, India - Purohit, Laxmikant; Sahu, Priyanka; Godale, Lata (National Journal of Community Medicine, 2017)
Background: Immunization is a proven tool for controlling and even eradicating disease. The vaccination coverage at present with EPI vaccines is far from complete despite the long-standing commitment to universal coverage. Aim and objectives: To assess immunization status and to study factors associated with it among 12-23 months children. Material and methods: It was community based descriptive cross sectional study conducted during January 2010 to December 2011 at Urban Health Centre of the Department of Preventive and Social Medicine. All 280 children of 12-23 months residing in slums of urban field practice area were included. Data was analyzed using SPSS software 16 version and openEpi Software Version 2.3. Results: 81.4% study subjects were fully immunized and 18.6% were partially immunized. Proportion of study subjects fully immunized differs significantly from those partially immunized with respect to religion and socioeconomic status. No significant association was observed between gender, type of family, mother’s education and birth order of child with immunization status. Conclusion: Majority of children were fully immunized indication good immunization coverage. There is need to evaluate different aspects of religion and socioeconomic status which are responsible for significant difference in immunization coverage.